Refinement of the Primate Corticospinal Pathway During Prenatal Development. (25th July 2019) - Ribeiro Gomes, Ana Rita; Olivier, Etienne; Killackey, Herbert P; Giroud, Pascale; Berland, Michel; Knoblauch, Kenneth; Dehay, Colette; Kennedy, Henry
Abstract: Perturbation of the developmental refinement of the corticospinal (CS) pathway leads to motor disorders. While non-primate developmental refinement is well documented, in primates invasive investigations of the developing CS pathway have been confined to neonatal and postnatal stages when refinement is relatively modest. Here, we investigated the developmental changes in the distribution of CS projection neurons in cynomolgus monkey ( Macaca fascicularis ). Injections of retrograde tracer at cervical levels of the spinal cord at embryonic day (E) 95 and E105 show that: (i) areal distribution of back-labeled neurons is more extensive than in the neonate and dense labeling is found in prefrontal, limbic, temporal, and occipital cortex; (ii) distributions of contralateral and ipsilateral projecting CS neurons are comparable in terms of location and numbers of labeled neurons, in contrast to the adult where the contralateral projection is an order of magnitude higher than the ipsilateral projection. Findings from one largely restricted injection suggest a hitherto unsuspected early innervation of the gray matter. In the fetus there was in addition dense labeling in the central nucleus of the amygdala, the hypothalamus, the subthalamic nucleus, and the adjacent region of the zona incerta, subcortical structures with only minor projections in the adult control.